(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to analyze health insurance expenditure for outpatient management of hypertension at the University Medical Center Ho Chi Minh City, Campus 2 from 2020 to 2023, and to identify factors associated with expenditure variation. Methods: A cross-sectional descriptive study was conducted using retrospective data extracted from the hospital’s health insurance payment database between 2020 and 2023. Statistical analyses were performed using Stata 16.0. Results: The average health insurance expenditure per outpatient case increased in 2021 and subsequently declined in 2023. Female patients had higher average costs than males in 2022 and 2023. Patients aged ≥ 80 years recorded the highest expenditures, as did those insured under government-funded health insurance schemes. Individuals with complications or comorbidities incurred significantly higher costs compared with those with primary hypertension alone. Differences between groups were statistically significant (p < 0.05). Conclusion: The average health insurance expenditure for outpatient hypertension management fluctuated across the study period and was influenced by demographic and clinical factors, including sex, age, insurance type, and disease condition.